The Complete Adventure of Peter Rabbit - Potter, Beatrix (Penguin Group, 1982)
A collection of the four stories relating all the adventures of Peter Rabbit and his mischievous cousin, Benjamin Bunny.
Keywords: Animals; Juvenile Fiction; Rabbits